2015
DOI: 10.1371/journal.pone.0128134
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Crataegus orientalis M Bieber. (Hawthorn) Extract Administration in Preventing Alveolar Bone Loss in Rats with Experimental Periodontitis

Abstract: The purpose of this animal study was to evaluate the effects of hawthorn (Crataeus orientalis M Bieber.) extract on serum oxidative status and alveolar bone loss in experimental periodontitis. Twenty-seven Wistar rats were assigned to one of the following groups: non- ligated+placebo (saline) (NL, n = 9), ligature only+placebo (saline) (LO, n = 9), and ligature and treated with hawthorn extract in saline (H, n = 9) (100 mg/kg orogastrically, once a day for 11 days). Periodontitis was induced by submerging a 4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…It is widely utilized in pharmaceutical preparations mainly because of its beneficial health effects and low toxicity . Hawthorn has been used as a treatment for digestive disorders, hyperlipidemia, high blood pressure, hypocholesterolemia, and for lowering serum cholesterol . Hawthorn is rich in biologically active phytochemicals such as flavonoids, polyphenols, terpenoids and organic acids, along with different essential minerals and proteins .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is widely utilized in pharmaceutical preparations mainly because of its beneficial health effects and low toxicity . Hawthorn has been used as a treatment for digestive disorders, hyperlipidemia, high blood pressure, hypocholesterolemia, and for lowering serum cholesterol . Hawthorn is rich in biologically active phytochemicals such as flavonoids, polyphenols, terpenoids and organic acids, along with different essential minerals and proteins .…”
Section: Introductionmentioning
confidence: 94%
“…10 Hawthorn has been used as a treatment for digestive disorders, hyperlipidemia, 11 high blood pressure, hypocholesterolemia, and for lowering serum cholesterol. 12,13 Hawthorn is rich in biologically active phytochemicals such as flavonoids, polyphenols, terpenoids and organic acids, along with different essential minerals and proteins. 14 As the findings of our previous studies have shown, hawthorn is able to inhibit PL and PA in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of C. orientalis M Bieber extract on serum oxidative status and alveolar bone loss in experimental periodontitis was studied in vivo and showed inhibitory effect on periodontal inflammation and alveolar bone loss by regulating total antioxidant (TAS)/oxidant (TOS) status and oxidative stress index levels in periodontal disease in rats when administered systemically (Hatipoglu et al, 2015). C. azarolus extract was active against herpes simplex virus-1 (HSV-1), and antiviral activity correlated with TPC (R = 0.773, p < 0.001) and free radical scavenging capacity (R = −0.684, p < 0.01) (Moradi et al, 2018).…”
Section: Skin Protective and Other Health Effectsmentioning
confidence: 99%
“…The fruits of C. orientalis are consumed as food . Pharmacological studies on C. orientalis have reported antithrombotic, antinociceptive, anti‐inflammatory, and antioxidant effects . C. tanacetifolia (Lam.)…”
Section: Introductionmentioning
confidence: 99%